Youth movements and Ireland, 1888-1914 - Power, Brendan (Trinity College (Dublin, Ireland). Department of History, 2013)
The methodologies used in this thesis have been empirical and statistical research. Employing these methods has situated these organisations in their proper historical context and provided vital information about the function they played in Ireland. It has been found that youth movements had diverse functions in the lives of members and these functions have highlighted wider social issues in Ireland. The major findings have been that youth movements were an example of how Irish society engaged with the emergence of the concept of adolescence and catered for members within this age group. These voluntary agencies attempted to provide members with the skills and values necessary to attain employment and provided outlets for, and a supervisory role over, the leisure time of adolescents in Ireland. This leisure time was facilitated by youth movements who provided numerous activities ranging from sport, camping, and drill, to games and reading rooms. These were activities otherwise unattainable to many members and ensured members received healthy exercise and regular retreats from the urban environment in which they lived. Youth movements sought to provide answers to the social concerns of the period ranging from fears of physical deterioration to deficiencies in educational facilities. They were significant in encouraging a civic sensibility amongst members and actively encouraged contributing to their local communities and engaged in charitable work. The military aspect of youth movements demonstrates the diffusion of military sentiments amongst voluntary agencies for adolescents in Ireland and provides an insight into how conventional military values were deemed desirable in society and that this was a topic that had entered civil discourse.
Embargo End Date: 2022-03-08
Keywords: Histories & Humanities, Ph.D.; Ph.D. Trinity College Dublin, 2013